Mechanical Properties Of Composite Biomass Briquettes (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In the handling and usage processes, sufficient density and durability of biomass (straw, read) briquettes should be provided. For the briquettes density standards determined the value ρ > 1.0 g cm-3. In ? the densification process usually fine grinded particles are used, what significantly increases energy consumption for stalk material cutting. Calculated energy consumption for common reed cutting to sizes less than 3 mm was > 7 kJ kg-1 but for size 20 mm it was approximately 1 kJ kg-1. The goal of the investigation was to obtain the necessary density and durability of briquettes of larger biomass particles by arranging them. The orientation of straw or reed stalks had to promote binding by the pressing operation. The long stalk linking, in the picture of coloured stalk briquettes sections, is good visible. Crushing force dependence on particle size for arranged structure briquettes is stated in laboratory experiments. The specific splitting force of arranged structure coarse chopped wheat straw and reed briquettes reaches value 35 N mm-1. It is approximately the same as industrially produced wood briquettes. Splitting force of the hemp stalk briquettes reaches 115 N·mm-1.